The Last Jihadist Battle in Syria: Externalisation and the Regional and International Responses to Hayat Tahrir al-Sham in Idlib - Bakkour, Samer (Religions, 2023)
When Hayat Tahrir al-Sham (HTS) seized Idlib, it alarmed and disturbed international observers. However, HTS is only one among a number of radical Islamist groups in a part of Syria that has become an incubator of Jihadism. As the last remaining redoubt of the armed opposition in the country, the governorate has become an international concern. Events have now reached an impasse, and the time is thus right for a reappraisal that steps back and considers contemporary developments in the wider context of ongoing events in the governorate. This article also places local developments in a wider context in another sense by considering how regional and international interventions contributed to HTS’s rise in the Idlib governorate. This is particularly important as external interventions by Turkey, Iran, Russia and the US have not only failed to establish a sustainable basis for peace by addressing the root causes of violence but have actually inflamed hostilities and exacerbated the various challenges involved in ending the conflict, which has at times taken on the appearance of a proxy war. In seeking to better theorise externalisation, this article draws on peacebuilding theory. This historical and political contextualisation seeks to contribute to an improved understanding of HTS’s rise and the means through which it can be most effectively combated in the future.